Validity and reliability of an incremental double poling protocol in cross-country skiers - Govus, A.; Marsland, F.; Martin, D.; Chapman, D. (Journal of Human Sport & Exercise, 2015)
This study determined the validity and reliability of an incremental double poling protocol performed on a Concept II ski-ergometer and validated this against an existing treadmill ski-striding protocol. Ten well-trained male cross-country skiers (age: 19 ± 1.4 y; height: 182 ± 72 cm; body mass: 76.0 ± 10.8 kg, whole body VO2Peak: 5.2 ± 1.0 L/min; upper body VO2Peak: 4.6 ± 1.0 L/min; upper body:lower body ratio: 87.2 ± 5.6%) performed four VO2Peak tests; one treadmill ski-striding test and three double poling ski-ergometer tests over five days. Test-retest reliability of the ski-ergometer protocol was determined for maximal oxygen consumption (VO2peak). The ski-ergometer test showed excellent reliability for VO2Peak (L/min) (coefficient of variation [CV] = 1.9%, 95% confidence limit [95% CL] [1.2, 4.7]; r = 1.00, [0.96, 1.00]) and UBPPeak (W) (CV = 1.4%, [0.9, 3.4]; r = 1.00, [0.97, 1.00]). Very strong correlations existed between the ski-ergometer and the ski-striding protocol for VO2Peak (r = 0.95, [0.76, 0.99]). The upper body ski-ergometer test provided valid and reliable measurements of ski-specific upper body aerobic power in well-trained male cross-country skiers.